2014
DOI: 10.1155/2014/519098
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Evaluation of Seven Different Disinfectants on Acrylic Resins

Abstract: Objective. The aim of this study was to evaluate alternative methods for the disinfection of denture-based materials. Material and Methods. Two different denture-based materials were included in the study. Before microbial test, the surface roughness of the acrylic resins was evaluated. Then, the specimens were divided into 8 experimental groups (n = 10), according to microorganism considered and disinfection methods used. The specimens were contaminated in vitro by standardized suspensions of Candida albicans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 53 publications
(63 reference statements)
4
44
0
15
Order By: Relevance
“…C. albicans and S. oralis were selected to test the antimicrobial activity of the different treatment strategies in vitro, because C. albicans and streptococci are microorganisms commonly used in in vitro studies . On the other hand, in vivo studies demonstrate that the most common microorganisms normally found on the prosthetic materials are Staphylococcus aureus, C. albicans , and streptococci, Neisseria, micrococci, Pseudomonas , bacilli , and Acinetobacter species .…”
Section: Discussionsupporting
confidence: 72%
“…C. albicans and S. oralis were selected to test the antimicrobial activity of the different treatment strategies in vitro, because C. albicans and streptococci are microorganisms commonly used in in vitro studies . On the other hand, in vivo studies demonstrate that the most common microorganisms normally found on the prosthetic materials are Staphylococcus aureus, C. albicans , and streptococci, Neisseria, micrococci, Pseudomonas , bacilli , and Acinetobacter species .…”
Section: Discussionsupporting
confidence: 72%
“…2,7,11,[16][17][18] These microorganisms were effective in contaminating the pliers tested in this study, as showed in group 4. This group was designed with the aim of verifying the existence of pliers' contamination.…”
Section: Discussionsupporting
confidence: 56%
“…White vinegar is frequently used in concentration of 50% and 100% for disinfection of toothbrushes and denture base acrylic resins. Da Silva FC et al, Yildirim-Bicer AZ et al, advocated the use of 100% vinegar for 10 minutes as denture disinfectant especially against Candida Albicans [21,23].…”
Section: Discussionmentioning
confidence: 99%